2011
DOI: 10.1002/app.34745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extractives on the performance properties of wood flour‐polypropylene composites

Abstract: In this study, the effects of extractives in wood flour on the physicomechanical properties of wood flour-polypropylene (PP) composites have been investigated. Three different solvents, hot-water (HW), 1% NaOH (AL), and dichloromethane (DM), were used to remove extractives in both poplar and eucalypt wood flour. The obtained results showed that mechanical properties of the composites were moderately enhanced on using extractive-free lignocellulosic materials in both the wood types. A large increase in the stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 8 publications
3
23
1
4
Order By: Relevance
“…Similar results were obtained from poplar [Sheshmani et al, 2012] and pine WF [Saputra et al, 2004]. Improvements in interfacial adhesion upon the removal of extractives were proposed to responsible [Sheshmani et al, 2012]. Another notable difference between wood species is the higher cellulose content of eucalyptus.…”
Section: Wood Chemistry Of Different Wood Speciessupporting
confidence: 72%
See 4 more Smart Citations
“…Similar results were obtained from poplar [Sheshmani et al, 2012] and pine WF [Saputra et al, 2004]. Improvements in interfacial adhesion upon the removal of extractives were proposed to responsible [Sheshmani et al, 2012]. Another notable difference between wood species is the higher cellulose content of eucalyptus.…”
Section: Wood Chemistry Of Different Wood Speciessupporting
confidence: 72%
“…Notably, birch and eucalyptus contain more extractives than other species. It was reported that the removal of wood extractives from eucalyptus WF improved the tensile and flexural properties of the resulting PP WPCs [Sheshmani et al, 2012]. Similar results were obtained from poplar [Sheshmani et al, 2012] and pine WF [Saputra et al, 2004].…”
Section: Wood Chemistry Of Different Wood Speciessupporting
confidence: 65%
See 3 more Smart Citations